Halal Certification Cooperation Between Indonesia and Malaysia: A Legal Analysis of the Principle of Reciprocity - Gumanti, Retna; Tomayahu, Nova Septiani; Lahay, Ivana Iring Restu (Hukum Keluarga Islam IAIN LANGSA, 2025)
This study was conducted to underscore the need for harmonization of halal certification systems between countries, particularly the challenges in achieving mutual recognition of halal certificates between Indonesia and Malaysia, based on the principle of reciprocity. The research aims to examine and analyze the legal aspects and normative barriers involved in implementing halal product assurance cooperation agreements between the two nations. A qualitative research method was employed, specifically doctrinal legal research, focusing on statutory regulations. The data analyzed were derived from secondary sources, including legal documents related to the international legal framework governing halal product assurance based on reciprocity, such as the Memorandum of Understanding (MoU), Government Regulation No. 39 of 2021, and JAKIM regulations. The findings reveal that a halal product assurance cooperation agreement has been established between Indonesia and Malaysia. Initially, halal certification for foreign products entering Indonesia was conducted through a business-to-business (B2B) mechanism. However, following the formal cooperation between the two countries, Indonesia's Halal Product Assurance Agency (BPJPH) and Malaysia’s Department of Islamic Development (JAKIM) signed a Memorandum of Cooperation (MOC) to facilitate mutual recognition of halal certificates. Notably, Article 123(1) of Government Regulation No. 39 of 2021 explicitly affirms that halal certification can be recognized through mutual agreements between countries, provided such recognition is reciprocal. This study contributes to the development of international legal theory, particularly in reinforcing national halal certification policies and advancing Islamic economic law through cross-border collaboration.